Characterization of novel diorganotin(IV) complexes with O,N,O donor ligand derived from carbohydrazide: X-ray crystal structure of [Ph₂Sn(H₂CBS)] - M A, Affan,; Y Z, Liew; Fasihuddin, B Ahmad,; Mustaffa, B Shamsuddin,; Bohari, M Yamin (Council of Scientific and Industrial Research (CSIR), 2007)
A new series of diorganotin(IV) complexes has been synthesized by the reaction of R₂SnCl₂ (R = Me, Bu and Ph) with O,N,O-tridentate carbohydrazone ligand derived from carbohydrazide. Three diorganotin(IV) complexes of carbohydrazone-bis(salicylaldehyde) ligand [H₄CBS, (1)] with R₂SnCl₂ have been synthesized by refluxing in the presence of base in 1:2:1 molar ratio (metal:base:ligand). All the complexes (2-4) have been characterized by different physico-chemical techniques like molar conductivity measurements, elemental analyses, UV-visible, IR and ¹H NMR spectral studies. All complexes (2-4) are non electrolytic in nature. Among them, diphenyltin(IV) complex (4) has also been characterized by X-ray crystallography diffraction analyses. In the solid state, the carbohydrazone ligand (1) exists as the keto tautomer. But in solution in the presence of base and organotin(IV) chloride(s), it is converted to the enol tautomer and is coordinated to the tin atom in its deprotonated enolate form. X-ray crystallographic analysis shows that the diphenyltin(IV) complex, [Ph₂Sn(H₂CBS)] (4), is five-coordinate and has a distorted trigonal-bipyramidal geometry with the ligand coordinated to the tin(IV) as a tridentate dinegative fashion through its phenolic-O, enolic-O and imine-N atoms. The general bond length order is: oxo < phenolato < enolato. The Sn-O (enolato) bond is longer than Sn-O (phenolato) bond by ~0.095 Å and is identical with Sn-O (carboxylate) bond. The crystal of [Ph₂Sn(H₂CBS)] (4) is triclinic with space group P-1 with a = 8.514(2)Å, b = 12.505(3)Å, c = 12.794(4)Å, ⍺ = 105.169(4)º, β = 107.639(4)º, ϒ = 96.232(4)º, V = 1226.5(6) Å³, Z = 1 and Dcalc = 1.541 mg/m³. The IR, UV and ¹H NMR data are consistent with all the diorganotin(IV) derivatives having similar geometry.